A redescription of Carcharhinus dussumieri and C. sealei, with resurrection of C. coatesi and C. tjutjot as valid species (Chondrichthyes: Carcharhinidae) - White, William T. (Zootaxa, 2012)
A taxonomic re-evaluation of the Carcharhinus sealei-dussumieri group using meristic and morphological data revealedthat this group consists of 5 species. Two species, Carcharhinus coatesi (Whitley, 1939) from northern Australia and prob-ably New Guinea and C. tjutjot (Bleeker, 1852) from Indonesian to Taiwan, are resurrected as valid species and togetherwith C. dussumieri and C. sealei are redescribed. Garrick’s lectotype designation of C. dussumieri and C. tjutjot areretained. A neotype for C. sealei, collected from the same locality as the holotype which was destroyed during World WarII, is designated. A fifth, possibly undescribed species (Carcharhinus sp.) is also noted from the Western Indian Oceanand its affinities briefly discussed. The four redescribed species are very similarly morphologically but can be distin-guished by a combination of meristic, morphological, dental and colour characters. The most important characters for dis-tinguishing these species are: vertebral counts, tooth counts, tooth morphology, shape of first dorsal and pectoral fins,second dorsal fin colouration, and mouth width. Two independent molecular studies have produced results which closely correlate with and support the findings of this study.